Higher Inpatient Morbidity and Mortality in Biliary Pancreatitis Compared to Hypertriglyceridemia-Induced Pancreatitis: A Nationwide Retrospective Study - Shaka, Hafeez (Cureus, 2020)
Introduction Hypertriglyceridemia (HTG)-induced pancreatitis is the third most common cause of acute pancreatitis after gallstone disease and alcohol. We analyzed data from the National (Nationwide) Inpatient Sample (NIS) with the aim of evaluating the outcomes of patients with HTG-induced pancreatitis when compared to those with biliary-induced pancreatitis. Methods The NIS database was sourced for data involving adult hospitalizations for HTG-induced pancreatitis in the United States between January 1, 2016 and December 31, 2017. The main outcome was mortality in patients with biliary pancreatitis vs HTG pancreatitis. Secondary outcomes were the incidence of sepsis, septic shock, non-ST-elevation myocardial infarction (NSTEMI), blood transfusion requirements, acute kidney failure, acute respiratory distress syndrome (ARDS), and length of hospital stay. Results A total of 575,230 patients were admitted with a diagnosis of acute pancreatitis, 18.2% of which were classified as having HTG pancreatitis. The in-hospital mortality for pancreatitis was 0.59%. Patients with HTG pancreatitis had lower odds of in-hospital mortality (adjusted odds ratio [aOR]: 0.74, 95% CI 0.582-0.934, p=0.012) compared to those with biliary pancreatitis. Patients with HTG pancreatitis had less odds of developing comorbid sepsis (aOR: 0.52, 95% CI 0.441-0.612, p<0.001), septic shock (aOR: 0.64, 95% CI 0.482-0.851, p<0.001), and NSTEMI (aOR: 0.70, 95% CI 0.535-0.926, p<0.001) and had less odds of requiring transfusion of blood products (aOR: 0.57, 95% CI 0.478-0.678, p<0.001) when compared to those with biliary pancreatitis. Patients with HTG pancreatitis also had a lower average length of hospital stay and lower total hospital charges compared to those with biliary pancreatitis. There was no statistical difference, however, in acute kidney failure and ARDS between the two groups. Conclusion Patients with HTG-induced pancreatitis possibly have better inpatient outcomes including mortality when compared to those with biliary-induced pancreatitis.